Molecular and allergenic characterization of recombinant tropomyosin from mud crab Scylla olivacea - Rosmilah Misnan (Tanjung Malim, 2021)
Molecular and allergenic characterization of recombinant tropomyosin from mud crab Scylla olivacea by Rosmilah Misnan